Pengaruh Penambahan Beberapa Jenis Pupuk Nitrogen Dengan Jarak Tanam Berbeda Terhadap Pertumbuhan dan Produksi Tembakau Deli (Nicotiana tabacum L.) - Syafrizal Syafrizal; Eva Sartini Bayu; Jonis Jonis Ginting (Universitas Sumatera Utara, 2015)
This research aimed were to study the growth and the production of deli tobacco with the additionsome kind of nitrogen fertilizer on 30 days after planted. This research was conducted in the land ofPT. Perkebunan Nusantara II (PTPN II) located in Kebun Klumpang, ±25 meter asl, in September-November 2013. This experiment in factorial based on randomized blok design with two factorsand three replication, consite of nitrogen fertilizer (0, 10 gram/plant Zwavelzure Amonium,15.6 gram/plant Calcium Amonium Nitrat, 5 gram/plant Zwavelzure Amonium + 8 gram/plantCalcium Amonium Nitrat) and double spacing planting distance (100x50x45 cm, 100x50x40 cm,100x50x35 cm). The parameters observed were plant height, stem diameter, number of leaves perplant, wet weight of leaf, length of leaf party Z, length of leaf party VA, width of leaf party Z, widthof leaf party VA, thickness of leaf party Z, thickness of leaf party VA. The results showed that thenarrow spacing plant has significant decrease parameters of plant height, stem diameter, the numberof leaf per plant and all production traits. The addition of nitrogen fertilizer significant increase allof the parameters except thickness of leaf party Z and thickness of leaf party VA. Interactionbetween plant spacing and addition of nitrogen fertilizer (100x50x45 cm + 10 gram ZA) showedsignificant effect of the width of leaf party Z on N1J0 (24,46 cm).Keywords: nitrogen fertilizer, deli tobacco, spacing planting distance.